2016
DOI: 10.1155/2016/2481659
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hyperglycemia and Insulin Resistance in the Development and Progression of Pulmonary Arterial Hypertension

Abstract: Pulmonary hypertension is a progressive disorder which often leads to right ventricular failure and death. While the existing classification system for pulmonary hypertension does not account for the impact of diabetes mellitus, evidence is emerging that suggests that diabetes is associated with pulmonary hypertension and that diabetes modifies the course of pulmonary hypertension. There is also growing radiographic, hemodynamic, biochemical, and pathologic data supporting an association between diabetes and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 44 publications
2
37
0
2
Order By: Relevance
“…Despite many publications demonstrating the adverse effect of hyperglycaemia on pulmonary endothelial or SMC function, there are a few clinical reports/articles discussing PH in diabetes (Table ; Grinnan et al . ). Movahed et al .…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 97%
“…Despite many publications demonstrating the adverse effect of hyperglycaemia on pulmonary endothelial or SMC function, there are a few clinical reports/articles discussing PH in diabetes (Table ; Grinnan et al . ). Movahed et al .…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 97%
“…In addition, Abernethy et al showed that DM is an independent predictor for the prognosis of PH patients [ 25 ]. Furthermore, Grinnan et al described that DM is an independent predictor for PH development, even when the other components of metabolic syndrome are controlled (odds ratio = 1.53; P < 0.001) [ 26 ]. However, most of the patients in these studies were in group 1 (pulmonary arterial hypertension) and patients in group 3 were rarely included, whereas all our study subjects had chronic respiratory disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the hypotheses mentioned above have not yet been confirmed, it is clear that the prediabetic condition will further damage the pulmonary vascular system and contribute to disease progression. High glucose concentrations induce mitogen-activated protein kinase/phosphatidylinositol 3-kinase(PI3K)-dependent upregulation of PDGF receptor-beta and potentiate migration and proliferation of smooth muscle cells (SMC) [ 20 , 21 ]. The inflammatory milieu associated with IR, as demonstrated by high levels of pro-inflammatory biomarkers such as C-reactive protein, interleukin-6, and myeloperoxidase, is thought to underlie the associated endothelial dysfunction and vascular disease [ 22 ].…”
Section: Discussionmentioning
confidence: 99%